A Review of Domed Cities and Architecture: Past, Present and Future. (7th September 2022) - Lutolli, Blerim
The goal of architecture is changing in response to the expanding role of cities, rapid urbanization, and transformation under changing economic, environmental, social, and demographic factors. As cities increased in the early modern era, overcrowding, urbanization, and pollution conditions led reformers to consider the future shape of the cities. One of the most critical topics in contemporary architecture is the subject of the future concepts of living. In most cases, domed cities, as a future concept of living, are rarely considered, and they are used chiefly as "utopian" visions in the discourse of future ways of living. This paper highlights the reviews of domed cities to deepen the understanding of the idea in practice, like its approach in terms of architecture. The main aim of this paper is to provide a broad overview of the need for domed cities in the face of pollution as one of the main concerns in many European cities. As a result, the significance of the reviews of the existing projects is focused on their conceptual quality. This review will pave the way for further studies in terms of future developments in the realm of domed cities. In this paper, the city of Celje, one of the most polluted cities in Slovenia, is taken as a case study for considering the concept of Dome incorporated due to the lack of accessible literature on the topic. This review's primary contribution is to allow architects to explore a broad spectrum of innovation by comparing today's achievable statuses against the possibilities generated by domed cities. As a result of this study, the concept of living under the Dome remains to be developed in theory and practice. The current challenging climatic situation will accelerate the evolution of these concepts, resulting in the formation of new typologies, which are a requirement for humanity.